Reconstructing Autonomy in Language Education
XVII, 264 p.
Keywords: This book uses fifteen grounded research projects to explore innovative self-reflexive approaches to autonomy in language education. It emphasizes the multi-voiced and contradictory complexity of pursuing autonomy in language education and includes commentary chapters to help readers engage with key issues emerging from the research.